Design Of Led Base Bell’s Palsy Therapy Device Using Microcontroller ATmega 8535 - Atika Hendryani; Hestu Azhim (Politeknik Kesehatan Kemenkes Jakarta II, 2019)
Bell’s Palsy is a disease that attacks the facial nerves to cause muscle paralysis on one side of the face, indicated by conditions one side of the face becomes stiff and difficult to move. Therapeutic devices are also very much needed to cure facial stiffness besides of giving medicines. One of the most widely used therapies is warm therapy, however, this therapy takes a long time and quite expensive too. This research proposed a simple and affordable bell’s palsy therapy device use LED temperature heating media and a time controller based on the microcontroller ATMega 8535. The test is carried out at a time and temperature series, the result shows the circuit accuracy reaches 100% on a 15-minutes test. Testing on temperature stability also showed achieving a stable temperature at 420C in the 15 minutes. Device function tests are only carried out at a time and temperature series, the patient safety test has not been carried out. So that it still needs to be improved in future studies, especially in safety mode.